A qualitative study of community perception and acceptance of biological larviciding for malaria mosquito control in rural Burkina Faso - Dambach, Peter; Müller, Margarida Melo Mendes Jorge; Sauerborn, Rainer; Becker, Norbert; Beiersmann, Claudia (BMC public health, 2018)
Vector and malaria parasite’s rising resistance against pyrethroid-impregnated bed nets and antimalarial drugs highlight the need for additional control measures. Larviciding against malaria vectors is experiencing a renaissance with the availability of environmentally friendly and target species-specific larvicides. In this study, we analyse the perception and acceptability of spraying surface water collections with the biological larvicide Bacillus thuringiensis israelensis in a single health district in Burkina Faso.
Published: 23 March 2018
Gesehen am 20.06.2018